Determination of Iron and Chromium by Precipitation from Homogeneous Solution Methods - Lakshminarayana, A.B.; Somasekhara Rao, Kaza; Singanan, M.; Sarat Babu, M.; Ratnakar, A. (Asian Journal of Chemistry, 2010)
Iron and chromium are precipitated quantitatively as their hydroxides by urea hydrolysis method from homogeneous solution. The pH for complete prcipitation for iron is 7.4 and for chromium is 7.2. The method has the advantage that the precipitates can be weighed as hydroxides after drying at 110ºC. These methods are advantageous over earlier methods since the precipitate need not to be ignited. Thermogravimetric and X-ray diffraction studies were made on the precipitates. These methods can be applied in the preparation of shift catalysts.